2016
DOI: 10.1016/j.aprim.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Detección y prevalencia del trastorno por uso de alcohol en los centros de atención primaria de Cataluña

Abstract: GP recognise AUD better in the elderly with worst health conditions than CIDI. AUD and alcohol dependence prevalence is high in primary health care centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…Similarly, previous European studies, such as PHEPA [21] (Primary Healthcare European Project of Alcohol), developed by the European Commission and the Department of Health of Catalonia, pointed to the need to promote alcohol prevention activities in the PC setting. In this context, a local study conducted in Catalonia [22] reflected that the lack of knowledge and specific training focused on the identification of at-risk alcohol use, hinders the implementation of the screening and treatment of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, previous European studies, such as PHEPA [21] (Primary Healthcare European Project of Alcohol), developed by the European Commission and the Department of Health of Catalonia, pointed to the need to promote alcohol prevention activities in the PC setting. In this context, a local study conducted in Catalonia [22] reflected that the lack of knowledge and specific training focused on the identification of at-risk alcohol use, hinders the implementation of the screening and treatment of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, various local studies have identified the level of knowledge among healthcare professionals regarding alcohol consumption. A study in Catalonia revealed a low level of knowledge in addressing alcohol consumption, primarily due to a lack of training in the prevention of alcohol consumption [40].…”
Section: Discussionmentioning
confidence: 99%
“…Desde una perspectiva sanitaria en cambio, de estos datos se deduce precisamente lo contrario: la necesidad de intervenciones más tempranas con la finalidad, precisamente, de evitar la progresión de la enfermedad a niveles de mayor severidad. En este punto merece la pena destacar los datos de un estudio reciente (Miquel et al, 2015) donde se aprecia que los médicos de atención primaria reconocen más la dependencia del alcohol en pacientes de mayor edad, mientras que las entrevistas semiestructuradas como la CIDI identifican a este grupo de pacientes de manera más temprana. Todo esto, sumado a los enormes costes que la enfermedad supone para la sociedad (Rehm et al, 2009), hace resaltar la idea de implementar el cribado universal de la dependencia alcohólica mediante herramientas diseñadas para tal efecto en atención primaria, tal y como ya recomiendan múltiples Pablo Barrio, Laia Miquel, Jose Moreno-España, Alicia Martínez, Lluisa Ortega, Lidia Teixidor, Jakob Manthey, Jürgen Rehm, Antoni Gual…”
Section: Discussionunclassified